1992
DOI: 10.1139/y92-268
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of spreading depression: a review of recent findings and a hypothesis

Abstract: Spreading depression of Leão (SD) can be provoked by numerous nonspecific mechanical, electrical, and chemical stimuli. A similar, if not identical, phenomenon can be provoked by hypoxia. SD is characterized by drastic depolarization of neurons, severe reduction of membrane resistance, and redistribution of ions across cell membranes. Glial cells also depolarize but retain membrane resistance. Tetraethylammonium hastens the onset of hypoxic SD but reduces the sustained potential shift and K+ outflow from cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(54 citation statements)
references
References 0 publications
3
48
0
2
Order By: Relevance
“…In this study, a platinum wire electrode was used for DC potential measurement. This electrode may not be ideal, but the waveforms recorded were con sistent with previously reported characteristics of CSD (McLachlan, 1992;Somjen et al, 1992). CSD may be generated by insertion of the electrode itself (Verhaegen et al , 1992) and by the microdialysis probe (Tomida et al, 1989), but this would have affected both groups equally.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, a platinum wire electrode was used for DC potential measurement. This electrode may not be ideal, but the waveforms recorded were con sistent with previously reported characteristics of CSD (McLachlan, 1992;Somjen et al, 1992). CSD may be generated by insertion of the electrode itself (Verhaegen et al , 1992) and by the microdialysis probe (Tomida et al, 1989), but this would have affected both groups equally.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, others have shown that when neurons lose their membrane potential and undergo spreading depression-like depolarization, extracellular Cl Ϫ decreases and intracellular Cl Ϫ increases (Phillips and Nicholson 1979;Jiang et al,1992), along with a general increase in membrane permeability (Hansen 1985;Tanaka et al, 1997). This can occur during hypoxia or OGD (Somjen et al 1992;Taylor and Weber, 1993;Obeidat et al, 2000). The source of the increase in intracellular Cl Ϫ during OGD cannot be established definitively because as the membrane potential approaches zero, an inwardly directed electrochemical potential is imposed on Cl Ϫ , driving Cl Ϫ into the cell through whatever conductance is available.…”
Section: Ogd Effects On Intracellular CL ؊ and Synaptic Transmissionmentioning
confidence: 89%
“…Maintenance of the electrochemical gradient largely depends on the Na + /K + ATP-ase activity and requires approximately 60% of the ATP produced. Therefore when energy production is impaired (e.g., during hypoxia), a rapid loss in ionic homeostasis occurs (Hansen, 1985;Müller and Somjen, 2000;Somjen et al, 1992). For example, the postsynaptic potential in hippocampal slices starts to decrease when ATP is lowered by 15% within 2 min following the initiation of hypoxia (Lipton and Whittingham, 1982).…”
Section: Atp Production and Brain Activitymentioning
confidence: 99%